Mighty Joe Young - Hartley, Ted (USA: Walt Disney Pictures [production company] ; Kuala Lumpur : Berjaya HVN Sdn. Bhd. [distributor])
In the classic tradition of heroic Disney adventures comes the extraordinary Mighty Joe Young - a thrilling story, full of excitement, friendship, courage and heart
Executive producer, Gail Katz ; editor, Paul Hirsch
Cast: Charlize Theron, Bill Paxton